Prarancangan Pabrik Amonium Nitrat dengan Proses Uhde Kapasitas 160.000 Ton/Tahun - Syafitri, Dita Odistya; , Ir. Haryanto AR., M.S; , Rois Fathoni, S.T. M.Sc. Ph.D (2017)
Ammonium nitrate factory was estabilished to meet the needs of ammonium nitrate in the country and abroad. It is based on the availability of raw materials and the need ammonium nitrate in several industrial sectors. Ammonium nitrate factory with materials ammonia and nitric acid is planned to be estabilished with a capacity of 160.000 ton/year. The process of making ammonium nitrate reaction with Uhde Process because this process is a very popular and has low investment cost to produce Low Dencity Ammonium Nitrate. The reaction performed on Bubbling Reactor. The mole ratio of Ammonia and Nitric Acid is 1:1,01. The temperature reaction is 140⁰C with a pressure on 3 atm which is exothermic reaction. Then the product will be concentrated by evaporate water with evaporator type Long Tube Vertical. Utility requirements in each year in the form of cooling water needs as much 34.932,92 kg/h, steam provider as much 7.117,45 kg/h, 145,49 kW electricity, and fuel as much 6,841 m3/h. The factory will be operate for 330 days. The economic analysis shows the amount is Rp 451.154.629.304,27 and working capital is Rp 223.966.932.637,34. Then profit before tax is Rp 80.543.222.890,54 and profit after tax is Rp 27.404.507.731,39. Percent Return on Investment (ROI) before tax is 28,93% and after tax is 20,25%. Pay Out Time (POT) before tax is 2,57 year and after tax is 3,31 year. Break Event Point (BEP) is 53,0% and Shut Down Point (SDP) is 33,65%. So, this plant is feasible to set up.